Globalna kemizacija - izziv javnemu zdravju - Vudrag, Marko (Zdravstveno varstvo, 2007)
Chemical safety can be defined as "prevention of short-term and long-term harmful effects of chemicals on human health and the environment" It is with this point in mind that Slovenia adopted a resolution on a national chemical safety programme, which establishes the conditions for implementing activities to rise the level of chemical safety and protection of public health and environmental quality. The importance of this issue cannot be overstressed given that large quantities of hazardous chemicals are produced, transported and utilized in Slovenia and elsewhere in the developed world. Significant changes are about to be made to curb the negative effects of chemical agents on human health and the environment. Public health plays a major role in the multidisciplinary processes aimed at increasing public awareness about these issues, as well as at offering health education and health promotion programmes, and assessing health risks. Our environment is mainly polluted with chemicals : some are known to cause immediate health harm and some are responsible for long-term health damage. Environmental experts, who are well aware of inadequate knowledge of the problem, have addressed and placed a high priority on the issue of chemical agents and chemical safety at numerous international conferences, perceiving it as a major challenge to public health.
Keywords: javno zdravje; kemikalije; onesnaževanje okolja; preprečevanje; škodljivi učinki; ukrepi